Description of Different Growth Stages of Sesamum indicum L. Using the Extended BBCH Scale - Attibayeba; Elie, Nsika-Mikoko; Serina, N`Kounkou Jean; Cerely Dianga, Julien Galet; Francois, Mandoukou-Yembi (Pakistan Journal of Nutrition, 2010)
The extended Biologische Bundesantalt and CHemische (BBCH) scale and its associated decimal code were used to describe the different growth stages of Sesamum indicum L. The study focused on different primary and secondary plant growth phases from germination to senescence. The use of a two-digit decimal code allowed the identification of the principal growth stages and their respective secondary stages. This approach suggests that this could be of great help to sesame growers and researchers for efficient planning of both management practices and experimental designs.